A Multidimentional Approach to Investigation of Living Standards of the Low-paid: Income, Wealth, Financial Stress and Consumption Expenditure - Wilkins, R; Hahn, M (My University, 2009)
This research explores the capacity of the income 'safety net' to provide adequate living standards for low paid workers. It examines levels of income, wealth, consumption expenditure and financial stress and explores the prevalence and persistence of low living standards among low-paid employees. The Melbourne Institute of Applied Economic and Social Research, University of Melbourne, were commissioned by the Australian Fair Pay Commission Secretariat to explore the capacity of the income 'safety net' to provide adequate living standards for low paid workers using Household, Income and Labour Dynamics in Australia (HILDA) Survey data from 2001 to 2006. The report finds that low-paid employees (defined as those employees earning less than 120 per cent of the hourly and weekly standard Federal Minimum Wage) are found throughout the distributions of household income, wealth and consumption expenditure. When living standards are defined by income and equivalised wealth, the proportion of adult employees that is low-paid and experiencing low living standards is no more than 3 per cent and 2 per cent if a consumption expenditure criterion is added. For a substantial minority of the low paid, their low living standards did not persist over the four years between 2002 and 2006. The report concludes that the prevalence of low living standards among the low paid in Australia is small and that, in the overwhelming majority of cases, employment is an effective mechanism for avoiding poverty, provided that sufficient hours are secured.
Australian Fair Pay Commission Research Report
Keywords: Income & Finance -- Wealth; Stress -- Financial stress; Housing; Income & Finance -- Income (Salary and Wages); Employment; Labour market; Income, wealth and finances; Employment; Income & Finance; Stress; Housing; Wealth; Financial stress; Income (Salary and Wages); Employment and unemployment; Income, wealth and finances